Anti-Angiotensin II Type 1 Receptor and Anti-Endothelial Cell Antibodies: A Cross-Sectional Analysis of Pathological Findings in Allograft Biopsies. Issue 3 (March 2017) - Philogene, Mary Carmelle; Bagnasco, Serena; Kraus, Edward S.; Montgomery, Robert A.; Dragun, Duska; Leffell, Mary S.; Zachary, Andrea A.; Jackson, Annette M.
Abstract : Background: This is a cross-sectional study designed to evaluate the histologic characteristics of graft injury in the presence of anti-angiotensin II type 1 receptor antibody (AT1R-Ab) and anti-endothelial cell antibody (AECA). Methods: Non-HLA antibody testing was included in the posttransplant evaluation for 70 kidney recipients. Biopsies were performed for cause for 47 patients and as protocol for the remaining 23 patients. Biopsy-proven rejection was defined according to the Banff 2009-2013 criteria. AT1R-Ab was measured on an ELISA platform. Patients were divided into 3 groups based on AT1R-Ab levels (>17, 10-17, and <10 U/ml). AECA was evaluated using an endothelial cell crossmatch (ECXM) in patients whose HLA antibody level was insufficient to cause a positive flow cytometric crossmatch. Results: AT1R-Ab levels were higher in patients diagnosed with antibody mediated rejection compared to those with no rejection ( P = 0.004). Glomerulitis (g) and peritubular capillaritis (ptc) scores were independently correlated with increased AT1R-Ab concentrations in the presence or absence of HLA-DSA ( P = 0.007 and 0.03 for g scores; p = 0.005 and 0.03 for ptc scores). Patients with a positive ECXM had higher AT1R-Ab levels compared to those with a negative ECXM ( P = 0.005). Microcirculation inflammation (MCI = g + ptc score) was higher in patients with a positive ECXM and with AT1R-Ab >17 U/ml, although this did not reach statistical significance ( P = 0.07). Conclusions: The data show an association between non-HLA antibodies detected in the ECXM and AT1R ELISA and microvascular injury observed in antibody mediated rejection. Abstract : The histologic characteristics of kidney graft injury are examined in terms of the presence of anti-angiotensin II type 1 receptor antibody (AT1R-Ab) and anti-endothelial cell antibody (AECA). The presence of AECA or AT1R-Ab correlates with microvascular injury observed in antibody-mediated rejection.